Boron concentration drives boron substructure and properties derivation in manganese borides - Shuailing Ma; Yuyue Pang; Kuo Bao; Min Lian; Shuying Wu; Chunyan Zhao; Chunhong Xu; Qiang Tao; Xingbin Zhao; Pinwen Zhu; Tian Cui (iScience, 2025)
Summary: Transition metal borides are important superhard multifunctional materials, in which boron concentration predetermined crystal and properties. However, the principles for effectively controlling properties through boron concentration remain unclear. Here, we reported the evolution of crystal structure, hardness, and magnetic behavior with boron concentration. Boron atoms tend to form isolated boron, boron chains, boron nets, and three-dimensional boron frameworks as boron concentration rises. The Vickers hardness initially increases from Mn2B to Mn3B4, then drops at MnB2, and finally reaches the highest value for MnB4, which suggest higher boron concentration is not a necessary factor for higher hardness, and the motifs of boron backbone are equally crucial. Moreover, boron sub-structure act as mediators of long-range ferromagnetic interactions, as evidenced by the evolution of magnetic behavior from paramagnetic, ferromagnetic, antiferromagnetic, and then paramagnetic behavior. These findings underscore the importance of manipulating boron backbone motifs to achieve high harness and superior magnetic properties.